ASSOCIATION BETWEEN RAINFALL AND PEDIATRIC HOSPITALIZATIONS FOR RESPIRATORY DISEASES IN INFANTS UNDER ONE YEAR OF AGE IN THE FEDERAL DISTRICT, BRAZIL, 2024 - Saldanha, Celso Taques; Peres, Alberto Stoessel Sadalla; Saldanha, Rafael Pimentel; Peres, Carolina Silva; Peres, Amanda Silva; Peres, Bianca Silva; Melo, Maria da Conceição da Silva Sousa; Braz, Luiza Caetano Machado Oliveira; Neves, Julliana Costa; Peres, Alberto Stoessel Silva; Maia, Lhanne Hanne Duarte; Carvalho, Mateus Braga (Seven Editora, 2025)
Introduction: The Federal District of Brazil has a tropical climate with marked rainy and dry seasons that influence childhood respiratory morbidity. The dry season, characterized by low humidity and increased airborne particles, is associated with worsening respiratory conditions in infants. Objective: To assess the association between rainfall and hospitalizations for respiratory diseases (ICD-10 J00–J99) among infants under one year of age in the Federal District, Brazil, during 2024. Methods: Ecological and retrospective study using data from SIH/DATASUS and INMET. A total of 5,266 respiratory hospitalizations of infants were analyzed. Pearson correlation and Mann–Whitney U test (p